Some Changes on Enzymic Activities, Compositional and Antinutritional Factors of an Indonesian Cowpea (Vigna Unguiculata (L) Walo) Cultivar undergoes Germination and A Mild Heating Process - harijono, Harijono; Mutiara, T.; Rakhmadiono, S. (Jurnal Teknologi Pertanian, 2001)
Changes during 48 hours germination at room temperature followed by a mild heating process on the seeds of an Indonesian cowpea cultivar  were evaluated. The results indicated that the activity of amylases and proteases increases until 36 hours of germination and then decreases.  The levels antinutritional factors, namely trypsin inhibitor, phytic acid, haemagglutinins were reduced somewhat, while the protein content and the digestibility value increase.  Germination for 36 hours followed by mild heating produces germinated seeds (10% moisture) with 26.27% protein, 9.63% reducing sugars, and relative enzymic activity levels of 37.63 (unit/mL) for amylase, and 78.81 (mmole tyrosine/minute/mg) for proteases.  The levels of phytic acid, haemagglutinins and trypsin inhibitors were reduced to about 50%, 40 % and 70% of their original levels respectively. The in vitro protein digestibility value is 74.79%.   Key words : cowpea, germination, changes, anti nutritional factors